Pemilihan Model Arsitektur Terbaik dengan metode backpropagation Dalam Menganalis Produksi Perikanan Laut - Ranjani; Suci Cahaya Mita; Indah Anggriyani; Poningsih (Bulletin of Information Technology (BIT), 2022)
The purpose of this study is the use of artificial intelligence to analyze the develop[pment of fishery production at TPI (Fish Auction Places) in Indonesia. Indonesia Logistic center throught the website. By using the Backpropagation method is a supervised artificial neural network where this method can assess the errors of each neuron after a set of data is processed. Tis also the goal of modifying the weights to train the neural network so that it can involve arbitrary input to output correctly. This research has several stages, namely training and testing wich will then be converted to several models to get the best results where the results found will later become the conclusions of the research.